Improving the Performance of Coffee MSMEs Through the Application of Technology and E-Marketing - Ana, Selvia Roos; Liyundira, Fetri Setyo; Carito, Danang Wikan (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2024)
help coffee MSMEs achieve long-term financial stability and sustainable performance. The strategy for implementing this service includes a participatory approach involving Ndeso Coffee MSME Owners who are actively involved in each stage through Focus Group Discussions. Furthermore, intensive training and mentoring by increasing in-depth knowledge about technology management and online marketing performance analysis. The results of the service, which are realized in the form of training and mentoring, show an increase in the quality of products produced by Ndeso Coffee MSMEs through the application of technology in the form of roasting machines. The impact of this can be seen in increasing taste consistency, production quantities, efficiency and effectiveness of time and energy. In terms of training and e-marketing assistance, Kopi Ndeso MSMEs already have online shop and social media accounts as media for sales, promotion and product branding. The training and mentoring activities carried out have had a positive impact on Ndeso Coffee MSMEs. Through these efforts, MSME Kopi Ndeso is able to develop and improve the quality of their products, utilize technology more effectively, and build a customer network in the digital realm.